(untitled) (Czech Journal of International Relations, 1999)
Nowadays an armed conflict need not necessarily be a war in the international sense of the word. The Jour Geneva Conventions, dating back to 1949, plus the two Supplementary Protocols of 1977 concerning the protection of the victims of armed conflicts react to the fact that armed conflicts can be of a different nature. These agreements cover all cases of a declared war or any armed conflict between two or more contracting parties, as well as cases when the state of war is not recognized by one of these parties. As distinct from the classic code of war, the current code of armed conflicts pertains even to armed conflicts which are not of an international nature. In international armed conflicts, it is not permitted to employ all types of means and methods of waging them. One of the general rules of the code of armed conflicts bans the use of weapons, ammunition, materials, and methods of waging war which by their very nature inflict excessive suffering or needless pain. Those who are to be protected are above all the combatants. The second general rule is the principle of a ban on making distinctions; this is significant for the protection of the civilian population. Under this principle, the civilian population and their property must not be the target of attack. Attacks must be confined to military objects alone. However, a broad interpretation of what is and what is not a military object can result in the justification of attacks (for example, attacks by air) directed against any property (e.g. also civilian) and against civilians. This applies to situations where entire systems (for example, the transport system) are the target of attack, and where even a number of civilian objects are hit. However, this interpretation is in contradiction with the pertinent provisions of the Supplementary Protocol of 1977. Failure to adhere to the rules of armed conflicts places an international legal responsibility on the state. Moreover, individual persons, too, bear a criminal responsibility. The responsibility of individual persons can be based on internal political jurisdiction but can also arise under international law. As a rule, only an international tribunal can give an objective judgment and possibly pass a sentence on whoever is responsible for the serious violation of the rules of armed conflicts. In the 1990s a Tribunal was set up to deal with crimes committed on the territory of the former Yugoslavia. In the same way, the statute on the establishment of an International Court of Justice in 1998, just like the Tribunal for crimes committed on the territory of the former Yugoslavia, embraces war crimes as well.